The expanding spectrum of diabetes - Sanjay Kalra,; Nitin Kapoor, (Journal of the Pakistan Medical Association, 2024)
The conventional approach views diabetes in binary terms: as type 1 or type 2 diabetes, with acute or chronic complications, needing either insulin or non-insulin agents. This, however, is an over-simplified impression. Diabetes may be a single eight-letter word, but it packs a wide spectrum of causative factors, clinical presentations, comorbid conditions, and complications.1 This is evident in the article published by Asma Ahmed et.al.2, who analyzed cases of diabetes ketoacidosis (DKA) presented to their center in Karachi.2 DKA is usually thought to be a complication of poorly controlled diabetes, but the authors highlight the susceptibility of persons with type 2 diabetes to DKA as well. This phenomenon, initially described as Flatbush diabetes, is common in people of South Asia ancestry.3 The patient may present in ketoacidosis or ketosis and then recover after the initial glucotoxicity and lipotoxicity have been corrected. COVID-19 is known to be a pro-diabetogenic condition, as it is associated with a poorer prognosis in persons with diabetes.4 This is clear from the study results, which showed the high frequency of DKA and the relatively poor prognosis of this complication in COVID-19 infected patients.2 Continued....